2011
DOI: 10.1088/0029-5515/51/11/112002
|View full text |Cite
|
Sign up to set email alerts
|

Internal plasma pressure peaking in low-shear open and closed magnetic confinement systems

Abstract: The plasma convective (flute-interchange) stability for low magnetic shear systems, with a low collisionality and a low beta, is considered in terms of the necessary and sufficient collisionless kinetic criterion. The magnetic confinement systems under consideration are axially symmetric mirrors equipped with outer divertors and inner field reversing rings (cusps, internal rings, high-beta cells) and closed multimirror traps. A simple approach is proposed for plasma stabilization resulting in a substantial ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The key result of [14] in comparison with previous works is that even for a partial compensation of the drift-induced space-charge separation due to the particle longitudinal motion, the plasma stability is improved: the allowable pressure profile is much steeper (figure 2).…”
Section: The Essence Of the Stabilization Effectmentioning
confidence: 84%
See 2 more Smart Citations
“…The key result of [14] in comparison with previous works is that even for a partial compensation of the drift-induced space-charge separation due to the particle longitudinal motion, the plasma stability is improved: the allowable pressure profile is much steeper (figure 2).…”
Section: The Essence Of the Stabilization Effectmentioning
confidence: 84%
“…This explains the shift of the peaking position for an anisotropic plasma [14,42], namely its position shifting towards the min dl for plasmas with prevailing longitudinal velocity and towards min λ max for plasmas with prevailing transverse velocity 3 . It is clear that the main contribution to the vanishing of ∫ G(λ, ψ)∂J /∂ψ dλ arises from the passing particles (low λ) in the first case and from the trapped particles (large λ) in the second case.…”
Section: The Peaking Position Control By Plasma Anisotropymentioning
confidence: 90%
See 1 more Smart Citation
“…For the particle distribution function F (ε, λ, ψ) = f (ε) G (λ, ψ) p m (ψ) (where ψ is the flux function, λ is the pitch angle, ε is the energy, and ∂f /∂ε should be <0) the kinetic criterion [13,[33][34][35][36][37] gives the stability condition (see [38,39] and [14,15]):…”
Section: Stable Pressure Profile Calculationmentioning
confidence: 99%
“…It has been found that a combination of the convex and the concave part of a field line provides a strong stabilizing action against convective (flute-interchange) plasma instability [14,15]. This results in internal peaking of the stable plasma pressure profile that is calculated from the collisionless kinetic stability criterion for any magnetic confinement system with a combination of mirrors and cusps.…”
Section: Introductionmentioning
confidence: 99%